The Student Problem Solving Skills in Science Subjects Based on Class Rankings : Keterampilan Pemecahan Masalah Siswa Pada Mata Pelajaran IPA Berdasarkan Peringkat Kelas - Sumiatiningsih; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2021)
The Problem solving skills are skills that must be possessed by students to solve a problem correctly and correctly in the learning process. Students with high achievement do not necessarily have high problem solving skills either. This study aims to describe students' problem-solving skills in simple aircraft material based on class rankings. This research method uses a qualitative method with a phenomenological approach. The research location was conducted at SMP Avisena Jabon, Kedungcangkring Sidoarjo. The data collection techniques used were tests, interviews, and documentation that had been tested for validity. The results showed that the problem solving skills possessed by students ranked 1 on all indicators were included in the very high category, problem solving skills possessed by students ranked 2 on all indicators were included in the high category, and problem solving skills possessed by students ranked 3 on all indicators included in the high category.